Reading together, learning together: The impact of literature circles on student engagement in reading - Pratama Irwin Talenta; Ulya Himawati (Jurnal CULTURE (Culture, Language, and Literature Review), 2023)
This study aims to provide educators with evidence-based insights that can inform instructional practices and ultimately enhance students' overall reading experiences. The implementation of literature circles as an instructional strategy has garnered significant attention within educational research, particularly in the domain of promoting student engagement in reading. This study uses a mixed-methods research design that combines both quantitative and qualitative approaches. This approach allows for a comprehensive exploration of the impact of literature circles on student engagement in reading while capturing both numerical trends and nuanced insights. The findings of this research illuminate the transformative potential of literature circles as a pedagogical strategy that positively influenced students’ engagement and enthusiasm. The researcher leverages the insights gleaned from this study to design and implement literature circles that foster collaborative learning, engagement, and intrinsic motivation. In conclusion, this study underscores the value of literature circles as a tool for educators aiming to create compelling and motivating reading experiences. By embracing the collaborative essence of literature circles and harnessing the potential of role assignments, the educators can guide students on a journey of exploration, discovery, and ownership within the realm of literature.